Mitigation translocation of red‐tailed hawks to reduce raptor–aircraft collisions. Issue 1 (24th August 2017) - Pullins, Craig K.; Guerrant, Travis L.; Beckerman, Scott F.; Washburn, Brian E.
ABSTRACT: Translocation of problematic individual animals is commonly used to reduce human–wildlife conflicts, especially to reduce the presence or abundance of raptors within airport environments, where they pose a risk to safe aircraft operations. Although this method has strong public support, there have been no scientific evaluations of its efficacy or to determine which factors might influence the return of translocated birds to the airport. We conducted a study to determine which biological and logistical factors might influence the return of red‐tailed hawks ( Buteo jamaicensis ) translocated from Chicago's O'Hare International Airport (ORD) during 2010–2013. We live‐captured and translocated red‐tailed hawks various distances from the ORD airfield and monitored for returning birds. We found the odds of hawk return increased by 2.36 (95% CI = 0.99–5.70) times for older birds (>1 yr of age) relative to younger birds (≤ 1 yr of age). Odds of hawk return went up 4.10 (95% CI = 0.75–22.2) times when translocations were conducted during the breeding season relative to the non‐breeding season. The odds of hawk return increased 11.94 (95% CI = 3.29–43.38) times for each subsequent translocation event involving the same hawk. The cost of 1 translocation event to the release sites that were 81, 121, 181, and 204 km from ORD was $213, $284, $362, and $426, respectively. Management programs that use release sites 80 km from the airport minimize translocation events to include only younger birds during the non‐breeding season, and undertake only 1 translocation event for an individual hawk would increase program efficacy and greatly reduce program implementation costs. The decision matrix regarding the use of a raptor trapping and translocation program involves a variety of biological, logistical, economic, and sociopolitical variables. This study represents an important first step in providing a scientific foundation for informing such management decisions. This article is a U.S. Government work and is in the public domain in the USA. Abstract : Airport raptor management programs that use release sites 80 km away from the airport minimize translocation events to include only younger birds during the non‐breeding season, and undertake only 1 translocation event for an individual hawk would increase program efficacy and reduce program implementation costs.